A case of adult cystic gastric duplication treated by laparoscopy - De Vinatea, José (2006)
The aim of the study was to evaluate the diagnosis difficulties and surgical treatment of this rare congenital disease. We describe a cystic gastric duplication case in a 42 year-old female patient who presented abdominal pain. Computed tomography and ultrasound revealed a cystic retrogastric mass. With the preoperative diagnosis of pancreatic cystoadenoma or pancreatic hydatid cyst the patient underwent laparoscopic surgery. A non-connected posterior wall stomach cyst was mobilized and resected. Histopathology examination revealed gastric duplication. In summary, treatment of this disease is surgical total excision and the laparoscopic approach is feasible.